A Metamodeling Approach for Planning Critical IoT Systems - Veiga, Ernesto; Kudo, Taciana; Bulcão-Neto, Renato (Cadernos do IME - Série Informática, 2025)
This paper presents a metamodeling approach to address the lack of methodological support in canvas model development, focusing on planning critical IoT systems. We introduce MM4Canvas - a metamodel that provides a solid foundation for developing structured and standardized canvas models, allowing for consistent reuse and extension across diverse project types. A proof of concept was conducted by instantiating a general-purpose canvas model based on MM4Canvas for project planning, aiming to establish a connection between this activity and the Requirements Engineering process. We extended this model to incorporate safety and security requirements for critical IoT systems. Our contribution demonstrates the metamodel’s capacity to support standardization, reuse, and extensibility in canvas-based project planning.